Mucous Membrane Pemphigoid in a Nonagenarian: A Case Report - Océane Babin de Lignac; Priscille Carvalho; Marion Carrette; Lucie Cellier; Philippe Courville; Billal Tedbirt (Annals of Geriatric Medicine and Research, 2023)
Mucous membrane pemphigoid is a rare autoimmune blistering disease characterized by post-bullous erosion of mucous membranes. Herein, we present a case of a nonagenarian man who was referred to our department of dermatology presenting with painful erosion of the buccal mucosa. Physical examination revealed palate erosion associated with erosion of the buccal mucosa. A diagnosis of mucous membrane pemphigoid was confirmed, and the patient was successfully treated with topical corticosteroids.